2020
DOI: 10.1111/inr.12619
|View full text |Cite
|
Sign up to set email alerts
|

Staying with nursing: the impact of conflictual communication, stress and organizational problem‐solving

Abstract: Aim: To predict nurses' intent to stay on the job as a function of organizational culture. Background: Organizational climate significantly contributes to retention of nurses. Communication by conflict and organizational control over problem-solving has not thoroughly been studied. Methods: A cross-sectional design was used with a randomly selected final sample of 367 nurses from regional hospitals in Hungary. Organizational climate, perceived stress, locus of control and self-esteem were assessed as main meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Formalised preceptor support is a key element of the NETP and NESP programs, which appears to be a very important element that has contributed to a positive experience for these nurses. Furthermore, evidence of early exposure to a positive workplace environment is pleasing given the importance of organisational culture and its links to early career employees' intention to stay (Ujváriné et al, 2020). In contrast, concerns are raised because of the lack of a sustained positive work environment and the overall lack of satisfaction with the nursing role, which is at odds with the report of continual satisfaction with professional support and the professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Formalised preceptor support is a key element of the NETP and NESP programs, which appears to be a very important element that has contributed to a positive experience for these nurses. Furthermore, evidence of early exposure to a positive workplace environment is pleasing given the importance of organisational culture and its links to early career employees' intention to stay (Ujváriné et al, 2020). In contrast, concerns are raised because of the lack of a sustained positive work environment and the overall lack of satisfaction with the nursing role, which is at odds with the report of continual satisfaction with professional support and the professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Stress and disillusion are two factors that lead to staff loss and contribute to burnout. 20,21 In response to the APP's complaint related to the second incident, the hospital Professional Staff Peer Review Committee recommended a Collegial Intervention by the medical director, citing institutional code of conduct and ethics and relevant policies/procedures. After the collegial intervention by the medical director, a written letter was provided to Dr AB, citing the meeting and documenting his assurance that there will be no further occurrences of the behavior that triggered the intervention.…”
Section: Incidentmentioning
confidence: 99%
“…In China, nurses’ work responsibilities, heavy workloads, tense relationships with patients, and other risk factors usually result in excessive job stress (Gu et al, 2019). A previous study suggested that nurses’ job stress was negatively correlated with their ITS (Ujvarine et al, 2020). According to a prior study carried out in rural Taiwan (Chao et al, 2015), the turnover intention of health care workers was positively correlated with their job stress.…”
Section: Introductionmentioning
confidence: 99%